Distribution and accumulation of Cadmium in different trophic levels affecting Serangium japonicum, the predatory beetle of whitefly Bemisia tabaci, biologically, physiologically and genetically: An experimental study - Khan, Muhammad Musa; Fan, Ze-Yun; Wang, Xing-Min; Qiu, Bao-Li (Journal of hazardous materials, 2024)
Cadmium (Cd) is a heavy metal that is of great concern in agroecosystems due to its toxicity to plants, herbivores, carnivores, and human beings. The current study evaluated the allocation and bioaccumulation of Cd from soil to cotton plants, cotton plants to herbivore pests, and herbivorous pests to a natural enemy predator. When soil was spiked with 100 mg/kg Cd, results demonstrated that cotton roots accumulated more Cd than the stems and leaves. The bioaccumulation of Cd was less in 4th instar larvae, pupa, and adults of Serangium japonicum than in Bemisia tabaci adults. The bioaccumulation in S. japonicum elongated the immature development period and reduced adult longevity, oviposition days, fertility, and total pre-oviposition duration. The net reproduction of S. japonicum was also reduced, as was female mature weight and feeding potential; as a result, Cd exposure could reduce the future population size compared to uncontaminated populations. There was decreased activity of the antioxidant enzymes (SOD, CAT, and POD) and energy-conserving lipids (glycogen, triglyceride, and total cholesterol) in Cd-contaminated S. japonicum compared to controls. The detoxifying enzyme activity of GST and P450 increased while AChE activity did not change. The qRT-PCR research showed that SOD1, CAT, POD, glycogen, and triglyceride gene expression was higher than in controls, whereas detoxification gene expression did not change. Our results indicate that Cd exposure has a physiological trade-off between its adverse effects on life history traits and elevated detoxification and antioxidation of S. japonicum, which could result from gene expression alteration. Further studies are needed to assess whether Cd exposure causes irreversible DNA damage in S. japonicum. [Display omitted] •Cd consumption affects the development and reproduction of S. japonicum.•Exposure to Cadmium adversely affects the population projection of S. japonicum.•Physiological trade-offs in Cd-exposed S. japonicum due to altered enzyme activities.•Altered gene expression patterns in response to Cd contamination.